Perilaku Makan Ibu Menyusui dengan Status Gizi Bayi 0-6 Bulan - Ratna Zahara; Tabitha Javingkan Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between the eating behavior of breastfeeding mothers and the nutritional status of infants 0-6 months in Central Helvetia. The method used is an analytical survey with a cross-sectional design. Sampling was done by simple random sampling method. The statistical test used for data analysis is the chi-square test. The results showed that the nutritional status of infants with a weight/age index was more in the normal category, namely 87.8%, and mothers with good eating habits were 32 respondents (78.0%). In conclusion, there is a significant relationship between the eating behavior of breastfeeding mothers and the nutritional status of infants 0-6 months. Keywords: Eating Behavior of Breastfeeding Mothers, Nutritional Status of Infants